2016
DOI: 10.1556/2006.5.2016.048
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Neural Basis of Avatar Identification in Pathological Internet Gamers and of Self-Reflection in Pathological Social Network Users

Abstract: Background and aimsInternet gaming addiction appears to be related to self-concept deficits and increased angular gyrus (AG)-related identification with one’s avatar. For increased social network use, a few existing studies suggest striatal-related positive social feedback as an underlying factor. However, whether an impaired self-concept and its reward-based compensation through the online presentation of an idealized version of the self are related to pathological social network use has not been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…Four out of five studies reported deficits in body image to be associated with GD [65, 119, 122, 125•]. It should, however, be noted that three studies were based on very small sample sizes (65,119,122; n addicted gamers < 20) and one other study assessed female gamers only [125•]. One online survey did not confirm this relationship [57•].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Four out of five studies reported deficits in body image to be associated with GD [65, 119, 122, 125•]. It should, however, be noted that three studies were based on very small sample sizes (65,119,122; n addicted gamers < 20) and one other study assessed female gamers only [125•]. One online survey did not confirm this relationship [57•].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the emotional self-concept revealed that addicted gamers rated themselves as having more difficulties in emotional intelligence, such as recognizing and expressing own emotions as well as in emotional regulation [65,85,90,96,119,141]. However, one study showed that gamers with higher usage showed improved emotional regulation but displayed more deficits in emotional expression and higher alexithymia as compared with those with less usage [103].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just blocking fat absorption is not addressing the many other issues related to obesity, whereby many genes and subsequent polymorphisms play important roles in the induction of aberrant cravings [25], enhancing brown fat synthesis [26], other addictions [27], and inducing metabolic anomalies [28]. …”
Section: Conventional Methods Do Not Comply With All Of the 4 Importamentioning
confidence: 99%